Risk factors and antibiotic therapy in P. aeruginosa community‐acquired pneumonia. Issue 4 (16th March 2015) - Sibila, Oriol; Laserna, Elena; Maselli, Diego Jose; Fernandez, Juan Felipe; Mortensen, Eric M.; Anzueto, Antonio; Waterer, Grant; Restrepo, Marcos I.
Abstract Background and objective Current guidelines recommend empirical treatment against Pseudomonas aeruginosa in community‐acquired pneumonia (CAP) patients with specific risk factors. However, evidence to support these recommendations is limited. We evaluate the risk factors and the impact of antimicrobial therapy in patients hospitalized with CAP due to P. aeruginosa. Methods We performed a retrospective population‐based study of >150 hospitals. Patients were included if they had a diagnosis of CAP and P. aeruginosa was identified as the causative pathogen. Univariate and multivariate analyses were performed using the presence of risk factors and 30‐day mortality as the dependent measures. Results Seven hundred eighty‐one patients with P. aeruginosa pneumonia were identified in a cohort of 62 689 patients with pneumonia (1.1%). Of these, 402 patients (0.6%) were included in the study and 379 (0.5%) were excluded due to health care‐associated pneumonia or immunosuppression. In patients with CAP due to P. aeruginosa, 272 (67.8%) had no documented risk factors. These patients had higher rates of dementia and cerebrovascular disease. Empirical antibiotic therapy against P. aeruginosa within the first 48 h of presentation was independently associated with lower 30‐day mortality in patients with CAP due to P. aeruginosa (hazard ratio (HR) 0.42, 95% confidence interval (CI): 0.23–0.76) and in patients without risk factors for P. aeruginosa CAP (HR 0.40, 95% CI: 0.21–0.76). Conclusions Risk factor recommended by current guidelines only detect one third of the patients admitted with CAP due to P. aeruginosa. Risk factors did not define the whole benefit observed due to empirical therapy covering P. aeruginosa.